2010
DOI: 10.1097/nen.0b013e3181f530ec
|View full text |Cite
|
Sign up to set email alerts
|

Early or Late-Stage Anti-N-Terminal Huntingtin Intrabody Gene Therapy Reduces Pathological Features in B6.HDR6/1 Mice

Abstract: Huntington disease (HD) is a progressive neurodegenerative disease caused by an expansion of a polyglutamine sequence in mutant huntingtin (mhtt) that produces abnormal folding and aggregation that results in the formation of nuclear and cytoplasmic neuronal inclusion bodies. Although the precise role of mhtt aggregates in the pathogenesis is unclear, attempts to reduce accumulated mhtt protein have ameliorated the phenotype in multiple cellular and in vivo HD models. Here, we provide critical results on intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 33 publications
0
42
0
Order By: Relevance
“…Of the iAbs tested, Happ1 ameliorated neuropathology in cell lines and conferred significant beneficial effects in a variety of motor and cognitive assays, significantly prolonging life span by 10 weeks in a mouse model of disease [45]. Another group delivering iAb C4 via intrastriatal AAV1 delivery demonstrated that early treatment of an HD mouse model, prevented cells from exhibiting nuclear aggregates and delayed aggregate accumulation [46]. …”
Section: Vectored Antibody Delivery For Neurodegenerative Diseasesmentioning
confidence: 99%
“…Of the iAbs tested, Happ1 ameliorated neuropathology in cell lines and conferred significant beneficial effects in a variety of motor and cognitive assays, significantly prolonging life span by 10 weeks in a mouse model of disease [45]. Another group delivering iAb C4 via intrastriatal AAV1 delivery demonstrated that early treatment of an HD mouse model, prevented cells from exhibiting nuclear aggregates and delayed aggregate accumulation [46]. …”
Section: Vectored Antibody Delivery For Neurodegenerative Diseasesmentioning
confidence: 99%
“…Quantitatively, both the size and number of HTT aggregates were significantly reduced at early-tomiddle stages of disease [48]. Confocal imaging with an anti-HA antibody, used to identify the presence of intrabody, confirmed that most transduced cells lack HTT aggregates initially.…”
Section: C4 Scfv In Mouse Modelsmentioning
confidence: 80%
“…For continuous production of intrabodies, viral delivery of genes encoding intrabodies has been shown to be effective in a fraction of cells, with persistence of signal over weeks-to-months [48,51]. Newer vectors may offer better spread and more efficient transduction, although localized and systemic immunogenicity remain concerns.…”
Section: The Challenge Of Deliverymentioning
confidence: 99%
“…Intrastriatal delivery of scFv-C4, using the adeno-associated virus vector (AAV2/1), resulted in a significant reduction in the size and number of mhtt aggregates in B6.Cg-HDR6/1 transgenic mice. However, the neuroprotective effect weakened both with severity of disease at time of injection, and with age beyond 6 months, although it does not disappear entirely [23]. Additional optimization of scFv-C4 is required for this intrabody to be of future use in clinical applications.…”
Section: Introductionmentioning
confidence: 99%